The Effectiveness of Socio-scientific Issues-Based Learning and Digital Literacy to Build Critical Thinking Skills for Students of Senior High School - Izzah, Noor; Anggraito, Yustinus Ulung; Ridlo, Saiful (Universitas Negeri Semarang, 2022)
The graduate’s profile of the middle education unit is expected to be able to achieve national educational goals which consider 21st-century skills such as critical thinking. One of the learning strategies which can build students' critical thinking skills is socio-scientific issues-based learning and digital literacy. This research aims to analyze the effectiveness of socio-scientific issues-based learning and digital literacy to build the critical thinking skills of the students of senior high school. This research is experimental research with a posttest-only control-group design. The samples in this study are the students of class X MIPA 1, X MIPA 2, X MIPA 7, and X MIPA 8, which are taken by random sampling technique. The data taken in this research is the data on critical thinking skills which are collected by test and non-test methods. The results of the research show that (1) based on the t-test, the results of the scores of Sig (2-tailed) < 0.05 mean that the scores of the student's critical thinking skills in the experimental classes are significantly different from the control class. The average scores of the student's critical thinking skills of the experimental classes are higher than the control class scores, so it can be interpreted that the student's critical thinking skills of the experimental classes are better than the control class, (2) the classical completeness in the experimental classes is higher than in the control classes. However, classical completeness in the experimental classes only reaches 65%, (3) the scores of the student response questionnaires in the good-very good category reach 97.2%, with details in the good category (75-84) reaching 59.7%, the very good category (85-100) reaching 37.5%. Thus, it can be concluded that socio-scientific issues-based learning and digital literacy on viruses and bacteria material is effective in building the critical thinking skills of high school students, however, it has not been effective in fulfilling classical completeness.